Synthesis and characterization of nanocrystalline zinc ferrite spinel powders by homogeneous precipitation method - Kant Sharma R.; Ghose R. (My University, 2025)
Single-phase nanocrystalline zinc ferrite (ZnFe2O4) spinel powders have been successfully synthesized by an easy homogeneous precipitation method in short precipitation time at low calcination temperature (250 °C). Characterization of the synthesized samples were carried out by powder X-ray diffraction, thermal gravimetric analysis, Fourier transform infrared spectroscopy, diffuse reflectance spectroscopy, surface area measurements, field emission scanning electron microscopy coupled with energy dispersive X-ray analysis and transmission electron microscopy. The spinel ZnFe2O4 powders consist of spherical nanoparticles with an average size of 5.2±0.61 nm. The antifungal activity of the nanocrystalline zinc ferrite powders was tested against pathogenic Candida albicans using the disc-diffusion susceptibility method. The nanocrystalline zinc ferrite powders exhibit strong antifungal activity against pathogenic C. albicans. © 2015 Elsevier Ltd and Techna Group S.r.l. All rights reserved.